Temporal changes in the incidence and pattern of central nervous system relapses in children with acute lymphoblastic leukaemia treated on four consecutive Medical Research Council trials, 1985-2001. - Krishnan, S; Wade, R; Moorman, A; Mitchell, C; Kinsey, SE; Eden, T; Parker, C; Vora, A; Richards, S; Saha, V (2010)
Despite the success of contemporary treatment protocols in childhood acute lymphoblastic leukaemia (ALL), relapse within the central nervous system (CNS) remains a challenge. To better understand this phenomenon, we have analysed the changes in incidence and pattern of CNS relapses in 5564 children enrolled in four successive Medical Research Council-ALL trials between 1985 and 2001. Changes in the incidence and pattern of CNS relapses were examined and the relationship with patient characteristics was assessed. The factors affecting outcome after relapse were determined. Overall, relapses declined by 49%. Decreases occurred primarily in non-CNS and combined relapses with a progressive shift towards later (> or =30 months from diagnosis) relapses (P<0.0001). Although isolated CNS relapses declined, the proportional incidence and timing of relapse remained unchanged. Age and presenting white blood cell (WBC) count were risk factors for CNS relapse. On multivariate analysis, the time to relapse and the trial period influenced outcomes after relapse. Relapse trends differed within biological subtypes. In ETV6-RUNX1 ALL, relapse patterns mirrored overall trends whereas in high hyperdiploidy (HH) ALL, these seem to have plateaued over the latter two trial periods. Intensive systemic and intrathecal chemotherapy have decreased the overall CNS relapse rates and changed the patterns of recurrence. The heterogeneity of therapeutic response in the biological subtypes suggests room for further optimization using currently available chemotherapy.